Youth Employment Insecurity and Development in Nigeria - Folorunsho Muyideen Ogunmefun; M. Y Okuneye (RIRAI Publisher, 2020)
The alarming rate of employment crisis among the youths is one of the manifestations of insecurity in Nigeria which has negatively eaten deep into developmental project of Nigeria. Youths are generally considered as the bedrock, prime-mover and cornerstone for achieving progressive development in any nations, Once, youths are denied opportunity to gainful employment they easily turn to negative innovations that may be detrimental to nation development. Unemployment as a social milieu will negate socio-political, economic and educational development of the nation. However, average Nigerian goes to sleep at night with one eye closed while other opened which may lead to poor manpower development, physical harassment delinquency, criminal activities, psychological trauma as a result of civil unrest among others.. Content systematic method of analysis was adopted in reviewing relevant publications from different search engines such as EMBASE, PDF, Scholarly Google, Scopus, JSTORS to supports the outcome of the inquiry. Social Contract Theory by Auguste Comte, Classical and neo-classical theories by Schumpeter, Boulding, were adopted to justify the causes, consequences and solutions to youths unemployment in Nigeria. On this ground, the following recommendations were made the Nigerian government, philanthropists and Non-governmental organizations should learn more on the value associated with social contract as the main determinant of social development Also, more recreational vocational and formal learning centers should be institutionalized to make room for employment accessibility, flexibility and employability among youths for creativity among others.